2009
DOI: 10.1111/j.1365-3156.2009.02360.x
|View full text |Cite
|
Sign up to set email alerts
|

Causes of morbidity among HIV‐infected children on antiretroviral therapy in primary care facilities in Lusaka, Zambia

Abstract: Objectives To describe the pattern of incident illness in children after initiation of antiretroviral therapy (ART) in a large public health sector in Lusaka, Zambia. Methods A systematic review was performed to extract data from medical records of children (i.e., under 16 years) initiating ART in the Lusaka, Zambia HIV care and treatment program. Incident conditions were listed separately and then grouped according to broad categories. Predictors for incident diagnoses were determined using univariate and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
18
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 21 publications
4
18
2
Order By: Relevance
“…Children who died exhibited the following high-risk characteristics: dual HIV/TB disease; young age (<6 months); recent ART initiation (<3 months on ART); and severe immunological suppression in infants <15 months of age. Similar trends in mortality have been noted in numerous studies, [18,28,30,31] providing further evidence of a focused time period among high-risk patients who may be ideal for a targeted intervention. Intensified surveillance of this population would ideally result in expedited referral to higher levels of care and decreased mortality.…”
Section: Discussionsupporting
confidence: 56%
“…Children who died exhibited the following high-risk characteristics: dual HIV/TB disease; young age (<6 months); recent ART initiation (<3 months on ART); and severe immunological suppression in infants <15 months of age. Similar trends in mortality have been noted in numerous studies, [18,28,30,31] providing further evidence of a focused time period among high-risk patients who may be ideal for a targeted intervention. Intensified surveillance of this population would ideally result in expedited referral to higher levels of care and decreased mortality.…”
Section: Discussionsupporting
confidence: 56%
“…This high rate of bacterial pneumonia despite adequate CD4 count has also been seen in the studies in other settings and offers evidence of continued immunologic deficits in the face of effective antiretroviral therapy in children. 3,5,15 The rate of herpes zoster in our study was higher than the rate reported in the 219C study 3 but was within the range reported in a more detailed examination of herpes zoster among a subset in the 219C study. 17 Interestingly, though, Hispanic ethnicity was associated with higher rates of herpes zoster in another U.S.-based study of HIV-infected children, which may be relevant to the Latin American population that we studied.…”
contrasting
confidence: 54%
“…3 The IR of bacterial pneumonia was higher than has been reported in the 219C study and other studies in the United States and Europe, 3,5 and was similar to the rate seen in the pre-HAART era in Spain 14 and the rate seen after 12 months of HAART in Zambian children. 15 While this should prompt further study, one explanation may well be the difficulty in diagnosing bacterial pneumonia and tuberculosis, especially in children, and the chance that episodes of nonbacterial respiratory illness or tuberculosis were recorded as bacterial. 16 Nevertheless, it is striking that 43% of children with an incident episode of bacterial pneumonia had a CD4% ‡ 25.…”
mentioning
confidence: 99%
“…However, infant HIV infections continue to occur: in utero (IU), intrapartum (IP), and postnatal (PN) (Mubiana-Mbewe et al, 2009). A study from 2007 to 2010 reported that 3,481 (12.2%) of 28,320 HIV DNA PCR tests from 5 provinces in Zambia were HIV positive (Torpey et al, 2012), though the authors saw an overall decrease in the proportions of positive PCR results over time- likely an indication of better prevention strategies.…”
mentioning
confidence: 99%